Barriers to Diabetes Self-Manegement During COVID-19 Pandemic: A Literature Review - Indah Nur Fatimah; Robiul Fitri Masithoh; Sri Margowati (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Diabetes Mellitus has become a public health problem that causes high rates of morbidity and mortality in the world. In controlling diabetes, diabetes self-management ia an important factor. Diabetes self-management aims to control glycemic, reduce the risk of complication, and optimize health status. Planning a healthy diet, physical exercise, selfmonitoring of blood sugar, and adherence to medication are some of the self-management diabetes behaviors. However, the current COVID-19 pandemic has affectes diabetes selfmanagement worldwide. This study aims to determine the barriers to self-management of diabetes during the COVID-19 pandemic. The research method uses a literature review design. Search sources for this research article are PubMed, ScienceDirect, and Google Scholar. Inclusion criteria were determined and appropiate analysis was used using the PICOS framework approach so that 12 articles were reviewed. Based on the results of a literature review on 12 articles, it shows that there are two categories of diabetes self-management barriers, namely internal barriers cosisting of lack of physical activity, unhealthy eating patterns, lack of knowledge about diabetes, lack of frequency of blood glucose monitoring, economic problems, and emotional problems. Meanwhile, external barriers found are to access health services and access to diabetes medicines. To improve diabetes self-management compliance during the pandemic, its is necessary to modify diabetes self-management. In addition, the use of inovations such as PROLANIS (Chronic Disease Service Program) and the ―Jemput sakit antar sehat‖ service program in the provison of health services and information during the pandemic. Knowing the various barriers to diabetes self-management can prevent similar incidents from happening in the future and further improve management quality.